Early life and juvenile cephalopods around seamounts of the subtropical North Atlantic: Illustrations and a key for their identification - Diekmann, Rabea; Piatkowski, Uwe; Schneider, Matthias (Institut für Meereskunde Kiel, 2002)
Berichte aus dem Institut für Meereskunde an der Christian-Albrechts-Universität Kiel No 326